“PELESETAN” DALAM PERTUNJUKAN WAYANG DALANG CENK-BLONK - Putu Devi Maharani (SPHOTA: Jurnal Linguistik dan Sastra, 2015)
Abstract Creativity in language is one aspect that caused Cenk Blonk shadow master’s show become interesting and attractive by Balinese people of all ages. Pun is one of speech play forms which found in some servant characters’dialogs of Cenk-Blonk puppeter. Despite theoretically pun means as something that deviates from the target, empirically the substances that showed in the pun that made ​​by Cenk Blonk mastermind fairly swooped and identical to its substance initial form. Structures and lexical forms that are used in his puns are very close to the social experience of the community. It caused the function of his speech play is not only as an entertainment jokes but also serves as social critique and culture identity. Key Words: Cenk-Blonk Performance, Speech Play, and Puns